Role of Hinduism in Creating Awareness About Sex and Its Related Functions. Issue 2 (April 2019) - Chandrasekar, P.; Gurusamy, P.
Abstract: Hinduism is otherwise known as Sanatana dharma, the oldest of all religions in the world. Its scriptures allow absolute freedom to the rational mind of human to choose the choice as per individual's choice wherein individual freewill is exercised. The present review article aims at how a Hindu is educated and guided by the scriptures to lead a harmonious life in the society in general and in particular the sexual functions as prescribed. The main focus of this article are the roles of individuals, families, community, the religious, and educational institutions, and the government to create awareness in the areas such sex, sexual functions and sexual problems among men and women. They are essentially important and needed for the healthy practices of sex in our Indian culture. To strengthen it further, some practical measures are suggested to bring in a change, especially adolescent period is a very exciting phase and they are facing lot of difficulties and challenges in the area of sex. Therefore, the educational institutions should conduct training and workshop for teachers, parents and students on reproductive health and healthy sexual function and the state and central should encourage to undertake the scientific research studies in different areas and groups, for different groups.